TANTANGAN PEMANTAU PEMILU DALAM MENJAGA HAK PILIH TAHUN 2024 - Ahmad, Masnia (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2024)
The aim of this research is to determine and analyze the challenges of election observers in maintaining voting rights in 2024. The method used in this research is qualitative, with secondary data sources using a literature study approach. The challenges faced by election observers in maintaining voting rights in the 2024 elections are divided into, namely challenges in the field and challenges based on social media. Specifically, the challenges faced in the field relate to administrative violations, violations of the code of ethics which are generally caused by money politics and certain interest tendencies, criminal violations caused by high fanaticism and identity politics, as well as other violations. Then, social media-based challenges are related to the widespread circulation of hoax information regarding the election.